Design and model test of flotation system and mooring posts of an amphibious house as adaptation for flooding - Castor, John Vincent D.; Soria, Carissa Marie T.; Hernandez, Jaime Y. Jr.; Orozco, Christian R.; Camelo, Jeane B. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
During storm or typhoon events vast areas are easily flooded, and large bodies of water surrounding the country contribute to even higher flood risks. Amphibious architecture is considered as a flood mitigation and climate change adaptation strategy that works well with the natural cycles of flooding of an area. Various countries such as Netherlands, Bangladesh, United States and U.K. have adapted amphibious houses in their flood-prone areas. In this study, a design of a foundation was done comprising the flotation and mooring system that will enable the structure, a low-cost residential house having a typical floor area of 20 m2, resting on it to float during flood and rest firmly on the ground during normal weather. Load analysis was done to determine the loads to be applied and will have significant effect on the structure's stability. The modular flotation prototype was constructed using waste materials selected and evaluated according to the following criteria: cost, availability, strength and sustainability, and performed satisfactorily when tested, being able to carry 579.08 kg at a submerged depth of 0.65 m. 13 modules are needed to support the total load of 93.712 kN of the house while maintaining 0.25 m allowance from its base to the floodwater surface. The flotation module was also tested for structural capacity when on ground and was able to carry a total of 1459.4 kg until significant displacement of the whole structure was observed. The optimum ssection that was modeled in STAAD for four mooring posts supporting the house was HSS6.875x0.5. An increase in the number of posts or section dimensions, or a decrease in maximum rise results to a decreased displacement. The computed capacity of the designed connection of the lock (0.5"-A36 steel plate and 3/4"-A325 bolts) is much greater than the resultant vertical force acting at the supports. The miniature model of the integrated system of flotation module and mooring posts demonstrated the feasibility of the final design and how amphibious house works.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Dwellings -- Flood damage; Flood damage prevention; Amphibious house